2018
DOI: 10.1007/s00415-018-9033-2
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of phenotype with genotype and protein structure in RYR1-related disorders

Abstract: Variants in the skeletal muscle ryanodine receptor 1 gene (RYR1) result in a spectrum of RYR1-related disorders. Presentation during infancy is typical and ranges from delayed motor milestones and proximal muscle weakness to severe respiratory impairment and ophthalmoplegia. We aimed to elucidate correlations between genotype, protein structure and clinical phenotype in this rare disease population. Genetic and clinical data from 47 affected individuals were analyzed and variants mapped to the cryo-EM RyR1 str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 95 publications
1
34
1
Order By: Relevance
“…Unfortunately, segregation analysis could not be performed because the proband's father was dead and his old mother lived in a different region of the country. The onset and distribution of muscle weakness in our patient involving only distal lower limbs in the fourth decade of life is quite different from that observed in individual patients carrying the same RYR1 variant [32] or the adjacent p.(Phe4808Asn) mutation [33][34][35] in which muscle weakness was proximal starting during early childhood [32,34,35] or there was only a susceptibility to MH without clinical myopathy [33]. In addition, he had a relevant cardiac history with atrial fibrillation which required ablation.…”
Section: Discussioncontrasting
confidence: 78%
“…Unfortunately, segregation analysis could not be performed because the proband's father was dead and his old mother lived in a different region of the country. The onset and distribution of muscle weakness in our patient involving only distal lower limbs in the fourth decade of life is quite different from that observed in individual patients carrying the same RYR1 variant [32] or the adjacent p.(Phe4808Asn) mutation [33][34][35] in which muscle weakness was proximal starting during early childhood [32,34,35] or there was only a susceptibility to MH without clinical myopathy [33]. In addition, he had a relevant cardiac history with atrial fibrillation which required ablation.…”
Section: Discussioncontrasting
confidence: 78%
“…Importantly, the detailed three-dimensional (3D) locations of disease-causing mutations in RyR1 and RyR2 and determination of structural changes associated with mutations that lead to disrupted Ca 2+ signalling will help in understanding the molecular process involved in regulating the ion channel gating mechanisms. In addition, the structure of potential drug binding sites opens the possibility of rational design of therapeutics to correct defective RyR channel function and restore healthy Ca 2+ signalling 20 , 25 , 31 , 32 . As an aside, the high-resolution structural studies have provided evidence supporting early insightful hypotheses that the functional consequences of some of the disease-causing mutations are caused by “unzipping” of essential inter-domain interactions and thereby favour the open unstable conformation of the channel 33 35 .…”
Section: The Impact Of High-resolution Structures Of the Ryanodine Rementioning
confidence: 99%
“…Additionally, some degree of dysfunction in calcium homeostasis and/or E-C coupling is a shared pathomechanism among RYR1-RD. The effects of specific RYR1 variants on these mechanisms depend on mode of inheritance and location on the gene [179]. Therapeutic development for RYR1-RD aiming to prevent RyR1 calcium leak may not be beneficial and could potentially be detrimental, in the context of dominant variants that reduce RyR1 calcium conductance or recessive variants that lead to a dramatic reduction in RyR1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…With nearly 700 RYR1 variations identified to date [176], availability and access to exome sequencing and genetic testing of the entire RYR1 gene can be credited for early and faster diagnosis [177], and expansion of the RYR1 disease spectrum [178]. A recent RYR1-RM natural history study [179] revealed that affected individuals born before the advent of next-generation sequencing (2004) were typically diagnosed as adults, while those born after 2004 were generally diagnosed in early childhood. Additionally, homozygous or compound heterozygous probands often exhibit a profound myopathic phenotype, while heterozygous probands might only experience a triggered phenotype.…”
Section: Delayed Diagnosismentioning
confidence: 99%